Sustaining Innovation on Aba Made Shoes: The Role of Government (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study examined the role of innovation and packaging on made in Aba shoes in the recent time following state government political intervention in the Aba shoe industry. The study has three specific objectives centering on innovation on made in Aba shoes, government commitment in made in Aba shoes and the core challenges confronting Aba made shoes. A cross sectional survey design, as well as a quantitative methodology where data is generated using structured questionnaire copies was adopted and administered to the accessible population of 150 shoe artisans in Ariaria Aba, Abia state. The study used descriptive analysis to analyze data. Arising from the results, it was found that innovation and creativity of Aba shoe artisans also help in improving the quality and brand of their product. It was also found that 43.3% those that are fore-front of innovation in Aba made shoes are SSCE holder artisans and that the immediate past state government played a vital tool in the promotion of made in Aba shoes. Following the finding, the study recommends for more state government commitment in the training of Aba shoe artisans especially in abroad, so as to improve their skills, innovation.